Microstrip antenna with DGS based on CSRR array for WiMAX applications - Ajay V. G.; Parvathy A. R.; Thomaskutty Mathew (Institute of Advanced Engineering and Science, 2019)
This paper reports a novel method for designing a miniaturized microstrip antenna with DGS based on CSRR array which operates in the frequency of 2.6GHz for low band WiMAX application. The proposed antenna is designed using ANSYS HFSS simulation software. The antenna with optimized parameters is fabricated using FR-4 substrate of thickness 1.6 mm. The simulated and measured performances of the antenna in terms of return loss, directivity and radiation patterns are presented in this work. When Complimentary Split Ring Resonators (CSRRs) array are placed on the ground plane, the resonant frequency is shifted to a lower value and patch size is reduced .The measurements were taken and compared with the simulated results. The performance characteristics obtained from the measurements show that the proposed antenna is suited for WiMAX application at 2.6GHz.